LEGALISASI PERKAWINAN BEDA AGAMA MELALUI PENETAPAN HAKIM - Defi Rahmi Fadhilah (UIN Imam Bonjol Padang, 2023)
This article aims to analyze the considerations of judges who grant requests for interfaith marriages. This type of research is normative legal research in the form of case studies with a content analysis approach. The cases analyzed in this study are case numbers 916/Pdt.P.2022/PN.Sby and 508/Pdt.P/2022/PN.JKT.SEL. The results of the study found that the judge's argument in granting interfaith marriages was that there were different forms of legalization of interfaith marriages. The Surabaya District Court judge legalized a valid interfaith marriage contract. Meanwhile, the judge at the South Jakarta District Court legalized interfaith marriage contracts. However, the South Jakarta District Religious Court did not grant marriage registration rights to applicants at the Population and Civil Registry Service Office.